Patient Perception of Physician Attire Before and After Disclosure of the Risks of Microbial Contamination - Enoch C. T. So; Faraday H. F. Fung; Joshua K. H. Yeung; Lilian H. Y. Chow; Julio S. H. Kwok; Ruby L. Y. Lam; Tommy C. Y. So; Faye S. M. Yu; Dana Vackova; Gilberto K. K. Leung (University Library System, University of Pittsburgh, 2013)
Background: The white coat is traditionally considered to be the appropriate attire for physicians but it may also be contaminated with microbes and act as a potential source of infection. We aimed to study patients' acceptance of physicians' attire, their underlying reasons, and their reactions to an educational intervention with regards to the risks of contamination.  Methods: We conducted a voluntary questionnaire survey at a university teaching hospital in Hong Kong from February to July 2012. 262 patient-responses from adult inpatients and outpatients across various specialties were analysed.  Results: White coats were highly favoured (90.8%) when compared with scrubs (22.1%), smart casual (7.6%) and formal (7.3%) wears. 'Professional image' and 'ease of identification' were the main attributes of the white coat. Most patients (92.2%) would prefer doctors washing their white coats every few days, whilst 80.9% believed that doctors were actually doing so. After patients were informed of the potential risk of microbial contamination, white coats remained as the most favoured attire (66.4%), but with scrubs doubling in popularity (45.8%). Smart casual (9.2%) and formal attire (4.6%) remain the least accepted.  Conclusion: Despite cross-infections being a significant concern within the healthcare environments, patients' predominant acceptance and perceived attributes towards the white coat were maintained after an educational intervention on the risks of microbial contamination.